Enhancing bifunctionality of CoN nanowires by Mn doping for long-lasting Zn-air batteries - Zhang, Yongqi (2020)
Tailoring the nanostructure and composition of transition metal nitrides is highly important for their use as potent low-cost electrocatalysts. Cobalt nitride (CoN) exhibits strong catalytic activity for oxygen evolution reaction (OER). However, its poor catalytic efficiency for oxygen reduction reaction (ORR) hinders its application in rechargeable zinc-air batteries (ZABs) as the air cathode. In this work, we deploy the effective strategy of Mn doping to improve both OER and ORR activity of CoN nanowires as the cathode material for ZAB. Theoretical calculation predicts that moderate Mn doping in cobalt nitride results in a downshift of the d-band center and reduces the adsorption energy of reaction intermediates. With ~10 at% Mn dopants, stronger catalysis activities for both OER and ORR are achieved compared to pure CoN nanowires. Subsequently, both aqueous and flexible quasi-solid-state ZABs are constructed using the Mn-doped CoN nanowires array as additive-free air cathode. Both types of devices present large open circuit potential, high power density and long-cycle stability. This work pushes forward the progress in developing cost-effective ZABs.